IMPACT OF EDUCATION ON PATIENT ANXIETY BEFORE CATARAC OPERATION IN EYE HOSPITAL NORTH SULAWESI PROVINCE - Herman J. Warouw; Semuel Tambuwun; Graciela M. Pandeirot (Jurnal Ilmiah Perawat Manado (Juiperdo), 2018)
Background. Anxiety is a problem that often occurs in the preparation of cataract surgery patients in the hospital. In some cases the surgery is delayed due to patient anxiety. This study aims to determine the effect of education on patient anxiety in the preparation of the implementation of cataract surgery in the Eye Hospital of North Sulawesi Province. Method: This research is an experimental study using a One Group Pretest-Posttest design to compare patient anxiety before and after education. The number of samples used is 27 people obtained using purposive sampling technique. Data collection is done by filling out the questionnaire and then analyzed using the Wilcoxon Signed Rank Test. Results: The data showed that the anxiety of patients before being given education was 88.9% having moderate anxiety, 88.9% and after being given the greatest education (59.2% category of mild anxiety. Statistical test results showed there were differences in anxiety between before and after provided education to patients with cataract surgery preparations, with a P-value = 0,000 (α <0.05) Conclusion: there is an influence of education on patient anxiety in the preparation of cataract surgery at the North Sulawesi Province Eye Hospital. It is expected that patients before surgery need to be given education or information clearly so that patients do not feel anxious in the operation.